Effects of Postharvest SO2 Treatment on Longan Aril Flavor and Glucosinolate Metabolites - Rob Md Mahfuzur; Dongmei Han; Jianhang Xu; Yuqiong Lin; Xiaomeng Guo; Tao Luo; Zhenxian Wu; Shilian Huang; Xinmin Lv; Junbin Wei (Plants)
SO2 fumigation treatment (commonly known as sulfur treatment, ST) is a key method in the postharvest preservation of imported and exported fresh longan fruits, effectively reducing pericarp browning and enhancing color. Nonetheless, distinctive aromas, often referred to as “sulfur flavor”, may develop in the aril during the extended preservation period. This study employed “Caopu” longan as the test material and patented SO2-releasing paper (ZL201610227848.7) as a treatment to perform a 35-day low-temperature (5 °C) storage of the fruit. The changes in glucosinolates (GSLs) and associated metabolites in the aril of treated fruit (ST) were examined utilizing ultra-high-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) detection and widely targeted metabolomics technology. The findings indicated that following 35 days of storage, nearly all control (CK) fruit pericarp turned to brown, resulting in an edible fruit rate of 75.41% and a commercial fruit rate of 0%. In contrast, the treated (ST) fruit demonstrated an edible fruit rate and a commercial rate of 99.44%, while the pericarp color changed from dark yellow-brown to light earthy yellow. The sulfur-containing metabolites identified in longan fruit aril predominantly consist of amino acids and their derivatives (60.44%), followed by alkaloids (15.38%), nucleotides and their derivatives (1.10%), and other types (23.08%), which include GSLs. SO2 treatment significantly reduced the content of oxidized glutathione in fruit aril but increased the content of GSLs and related amino acids and their derivatives. Via screening, 19 differential sulfur-containing metabolites were obtained between ST and CK, including 11 GSLs. The identified differential metabolites of GSLs were all increased, primarily comprising aliphatic GSLs, such as 1-hydroxymethyl glucosinolate, 2-Propenyl glucosinolate (Sinigrin), and 4-Methylsulfinylbutyl glucosinolate (Glucoraphanin). Pathway analysis showed that these differential metabolites were mainly involved in coenzyme factor synthesis, cysteine and methionine metabolism, and amino acid synthesis, among other pathways. To the best of our knowledge, this is the first study to reveal the causes of the special flavor of longan aril after SO2 treatment, which is a great concern for longan consumers. Moreover, this study provides a scientific basis for exploring the reasons and mechanisms for the development of the sulfur flavor in the SO2-treated fruits during postharvest storage.